Bonus of the azul and gol companies in relation the collection of “IPVA” about its aircraft (Revista Brasileira de Contabilidade e Gestão, 2020)
The Imposto sobre Propriedade de Veículos Automotores (IPVA) is the responsibility of thestates and the Federal District, that is, the tax is governed by state legislation. There werediscussions in the Supreme Federal Court (STF)regarding the incidence of this tax on vesselsand aircraft, however, the STF decided to exempt the collection of IPVA on the assets inquestion. The purpose of this research is the estimated presentation of the tax disbursement of airtransport companiesif the collection of IPVA on their aircraft was instituted. With that, thisresearch searched in the financial statements of the air transport companies Azul and Gol, therespective values corresponding to the possessions of their aircraft. Upon this amount wasapplied and calculated at the IPVA rate. The rate used corresponds to the host state of eachairline Azul and Gol, which are São Paulo and Rio de Janeiro respectively. Both states have a4% rate for levy IPVA for land vehicles. The estimated tax disbursement that the air transportcompanies Azul and Gol build in 2019 regarding the collection of IPVA on their aircraft wouldbe R$ 261.415,84 and R$ 131.057,04 respectively. For companies, this tax would be seen as anadditional tax liability to be paid,in others words, for them it would be considered negatively.However for the states that received this amount, it would help to strengthen their finances.
Keywords: Aircraft Taxation; Costs; Aircraft; IPVA